Survey of underwater robot positioning navigation. (September 2019) - Wu, Yinghao; Ta, Xuxiang; Xiao, Ruichao; Wei, Yaoguang; An, Dong; Li, Daoliang
Abstract: Underwater robot positioning and navigation achieve autonomous underwater robot movement based on the premise that positioning obtains the coordinates of the relative position of the underwater robot using a sensor, and navigation yields a known location to the destination path planning. Due to the location of an underwater robot and the complex and changing environment in which it operates, it is difficult to achieve precise positioning using the traditional positioning method. This paper systematically analyzes and summarizes several typical localization and navigation methods of underwater robots, such as multisensor information fusion technology, underwater acoustic localization and navigation methods, GPS buoy, underwater vision, SLAM and coordinate localization and navigation of multiple underwater robots. Multisensory information fusion technology integrates the advantages of the above methods, enhances the system stability and robustness, overcomes the disadvantages of traditional positioning and navigation, and enables the autonomous navigation and positioning of underwater robots. Underwater acoustics enable flexible and convenient positioning, whereas GPS can achieve high-precision and high-positioning navigation information, and visual positioning effectively overcomes the problem of error accumulation. Multirobot cooperative positioning resolves the problem of positioning failure caused by the collapse of a single system and completes complex tasks that cannot be completed by a single robot, thus enhancing the stability and robustness of the system. This paper systematically describes the realization of these methods, presents an actual analysis of their respective advantages and problems, and discusses the development of the field of research prospects and application prospects.